2019
DOI: 10.5946/ce.2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nasobiliary Tubes and Biliary Stents in Management of Patients with Bile Leak after Liver Transplantation: A Systematic Review

Abstract: Background/Aims Bile leak is one of the most common complications of liver transplantation. The treatment options for bile leaks include conservative management, surgical re-intervention, percutaneous drainage and endoscopic drainage. We aimed to perform a systematic review to identify the efficacy of endoscopic treatment in the resolution of post-transplant bile leaks. Methods Two independent reviewers performed systematic literature search in PubMed, ISI Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Biliary complications are quite common after LT, with a global incidence ranging from 2% to 19% [126]. These complications are related to significant postoperative morbidity and mortality rates after LT [127,128].…”
Section: Biliary Complicationsmentioning
confidence: 99%
“…Biliary complications are quite common after LT, with a global incidence ranging from 2% to 19% [126]. These complications are related to significant postoperative morbidity and mortality rates after LT [127,128].…”
Section: Biliary Complicationsmentioning
confidence: 99%
“…21 Treatment of bile leaks with an ERCP and plastic stent placement resolves early bile leaks in 82%-95% of cases. 22,23 Similarly, ERCP with serial balloon dilation and exchange of biliary stents every 3 mo for 1-2 y is the first-line therapy for most anastomotic biliary strictures. One systematic review of 440 liver transplant patients with anastomotic biliary strictures found that those treated for >12 mo with serial dilation and stent exchange resolved their strictures 97% of the time, 24 and another large series of 69 patients found that 94% of these biliary strictures could be successfully resolved with endoscopic management.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic choledochal exploration with primary suture combined with C tube drainage. Some studies have shown that intraoperative or preoperative placement of ENBD combined with primary closure suture can drain bile, reduce bile duct pressure, decrease the occurrence of bile leakage, and support the bile duct to reduce biliary stricture [13,14]. Some studies have shown that laparoscopic choledochal exploration with primary closure suture combined with PTCD tube is effective in reducing operative time and postoperative hospitalization compared with T-tube drainage [15] However, Primary suture combined with PTCD can also reduce bile drainage and biliary pressure, which can reduce the incidence of postoperative bile leakage and biliary stricture to a certain extent, but there are more steps to be performed, longer time to carry the tube, and the placement of PTCD has the corresponding complications.…”
Section: Simple Primary Closure Combined With External Drainagementioning
confidence: 99%